2018
DOI: 10.1038/s41598-018-23330-5
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: Cross sectional evaluation of the gut-microbiome metabolome axis in an Italian cohort of IBD patients

Abstract: A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
1
2
0
1
Order By: Relevance
“…Moreover, the prevalence of Faecalibacterium negatively correlated with phenethylamine levels, suggesting a role of this metabolite in the pathogenesis of inflammatory conditions. 5 Furthermore, in RM at 56 weeks of treatment, the baseline level of 3-hydroxybutyric acid at week 0 decreased at 56 weeks of treatment in our study. 3-Hydroxybutyric acid was found to attenuate stress-induced inflammatory responses and increase SCFA production in an in vitro colonic microbial model.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…Moreover, the prevalence of Faecalibacterium negatively correlated with phenethylamine levels, suggesting a role of this metabolite in the pathogenesis of inflammatory conditions. 5 Furthermore, in RM at 56 weeks of treatment, the baseline level of 3-hydroxybutyric acid at week 0 decreased at 56 weeks of treatment in our study. 3-Hydroxybutyric acid was found to attenuate stress-induced inflammatory responses and increase SCFA production in an in vitro colonic microbial model.…”
Section: Discussionsupporting
confidence: 43%
“…1 Several studies have suggested that the gut microbiota and its metabolites can affect the development and progression of IBD. 25 Metabolic alterations [such as those in bile acids and short-chain fatty acids (SCFA)] have been identified in biofluids of patients with UC and Crohn’s disease (CD) in many studies and may provide novel therapeutic solutions. 6,7 Fecal samples can serve as reliable and practical sources to determine the composition of metabolites derived from the gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of polyamines may be toxic and are associated with several diseases. Cadaverine levels have also been directly associated with Escherichia in Crohn's disease patients, which suggests the presence of intestinal inflammation (22). While their specific roles are largely unknown, they may have a potential role in the occurrence and development of BMJ.…”
Section: Discussionmentioning
confidence: 99%
“…Una dieta alta en AG saturados se ha asociado con una reducción en la diversidad de la MI (Sonnenburg, Tremaroli, Kovatcheva, Cani & Backhed, 2016) con aumento de bacterias patógenas (Fava et al, 2013), desarrollo de inflamación intestinal (Devkota et al, 2012), resistencia a la insulina e inflamación sistémica de bajo grado . Por otro lado, los efectos de los ácidos grasos poliinsaturados (AGPI) dependen del tipo de AGPI, ya que los AGPI ω-6 pueden provocar disbiosis asociada con inflamación intestinal (Prossomariti et al, 2017) y obesidad (Kaliannan, Wang, Li, Kim & Kang, 2015), mientras que los AGPI ω-3 pueden revertir la disbiosis y promover una microbota saludable (Santoru et al, 2017), además de servir como precursores de sustancias antiinflamatorias capaces de mantener la integridad del epitelio, por lo que están asociados con la prevención o tratamiento de ciertas enfermedades (Li et al, 2008).…”
Section: Oligosacáridos De La Leche Materna (Hmo)unclassified